Chlorine and fluorine partition coefficients and abundances in sub-arc mantle xenoliths (Kamchatka, Russia): implications for melt generation and volatile recycling processes in subduction zones - Bénard, A.; Koga, K. T.; Shimizu, N.; Kendrick, M. A.; Ionov, D. A.; Nebel, O.; Arculus, R. J. (Geochimica et Cosmochimica Acta, 2017)
We report chlorine (Cl) and fluorine (F) abundances in minerals, interstitial glasses, and melt inclusions in 12 andesite-hosted, spinel harzburgite xenoliths and crosscutting pyroxenite veins exhumed from the sub-arc lithospheric mantle beneath Avacha volcano in the Kamchatka Arc (NE Russia). The data are used to calculate equilibrium mineral-melt partition coefficients (D) for Cl and F relevant to subduction-zone processes and unravel the history of volatile depletion and enrichment mechanisms in an arc setting. Chlorine is ∼100 times more incompatible in pyroxenes (D = 0.005–0.008 [±0.002–0.003]) than F (D = 0.50–0.57 [±0.21–0.24]), which indicates that partial melting of mantle sources leads to strong depletions in Cl relative to F in the residues. The data set in this study suggests a strong control of melt composition on D , in particular HO contents and Al/(Al + Si), which is in line with recent experiments. Fluorine is compatible in Ca-amphibole in the ‘wet’ sub-arc mantle (D = 3.5–3.7 [±1.5]) but not Cl (D = 0.03–0.05 [±0.01–0.03]), indicating that amphibole may fractionate F from Cl in the mantle wedge. The inter-mineral partition coefficients for Cl and F in this study are consistent amongst different harzburgite samples, whether they contain glass or not. In particular, disseminated amphibole hosts much of the Cl and F bulk rock budgets of spinel harzburgites (D up to 14 and D up to 40). Chlorine and fluorine are variably enriched (up to 1500 ppm Cl and 750 ppm F) in the parental arc picrite and boninite melts of primitive pyroxenite veins (and related melt inclusions) crosscutting spinel harzburgites. Based on the data in this study, the main inferences on the behaviour of Cl and F during melting and metasomatic processes in the sub-arc mantle are as follow: (i) Melting models show that most depleted mantle protoliths of intra-oceanic arc sources can have extremely low Cl/F (0.002–0.007) before being overprinted by subduction-derived components. (ii) Chlorine has a higher percolation distance in the mantle than F. Even for small fluid or melt volumes, Cl and F signatures of partial melting are overprinted by those of pervasive percolation, which increases Cl/F in percolating agents and bulk peridotites during chromatographic interaction and/or amphibole-forming metasomatic reactions. These processes ultimately control the bulk Cl and F compositions of the residual mantle lithosphere beneath arcs, and likely in other tectonic settings. (iii) Fluxed melting models suggest that Cl enrichment in arc picrite and boninite melts in this study, and in many arc melt inclusions reported in the literature, could be related to the infiltration of high Cl/F fluids derived from subducted serpentinite or altered crust in mantle wedge sources. However, these high Cl/F signatures should be re-evaluated with new models in light of the possible overprint of pervasive percolation effects in the mantle. The breakdown of amphibole (and/or mica) in the deep metasomatised mantle at higher pressure and temperature conditions than in the slab may explain, at least in part, the positive correlations between F abundances and Cl/F in primitive arc melt inclusions and slab depth.